Comparative study of the influence of the reorganization energy on the hole transport of two four-cyclic arenes - Kania, Sylwester; Kuliński, Janusz; Sikorski, Dominik (Wydawnictwo Politechniki Łódzkiej, 2017)
Application of the method of quantum-mechanical calculations allowed the determination of the reorganization energy of the molecules of tetracene and p-quaterphenyl and the estimation of the transfer rate integral between neighbouring molecules present in the solid state. Comparison of the transfer rates for holes with the values of the mobility, obtained experimentally for the polycrystalline tetracene layers and p-quaterphenyl layers vaporized in the vacuum in the similar conditions indicate that the molecule’s structure possess the dominate impact on the conductivity of the thin layers of these compounds.

Zastosowanie metody obliczeń kwantowo-mechanicznych pozwoliło na wyznaczenie energii reorganizacji cząsteczek tetracenu i p-kwaterfenylu oraz oszacowanie wartości całki przenoszenia elektronu pomiędzy sąsiadującymi cząsteczkami znajdującymi się w fazie stałej. Porównanie szybkości przenoszenia dziur z wartościami ruchliwości dziur w polikrystalicznych warstwach tetracenu i p-kwaterfenylu naparowanych w próżni w identyczny sposób wskazuje na dominujący wpływ budowy cząsteczki na przewodnictwo cienkich warstw tych związków.
Studium porównawcze wpływu energii reorganizacji na przewodnictwo dziur dwu czteropierścieniowych arenów
Keywords: reorganization energy; tetracene; p-quaterphenyl; carrier mobility; energia reorganizacji; przewodnictwo; tetracen; mobilność nośnika